A randomized, single-blind, Phase I trial (INVICTAN-1) assessing the bioequivalence and safety of BI 695502, a bevacizumab biosimilar candidate, in healthy subjects. (3rd August 2017) - Hettema, Willem; Wynne, Christopher; Lang, Benjamin; Altendorfer, Mario; Czeloth, Niklas; Lohmann, Ragna; Athalye, Sandeep; Schliephake, Dorothee
ABSTRACT: Objectives : This Phase I trial (INVICTAN®-1) evaluated three-way bioequivalence and safety of BI 695502 a bevacizumab biosimilar candidate, and reference product bevacizumab from two sources (US-approved Avastin®, Genentech; EU-approved Avastin, Roche). Methods : Healthy male subjects ( N = 91) were randomized 1:1:1 to receive a single intravenous infusion of 1 mg/kg of BI 695502 or US- or EU-approved Avastin. An interim analysis was planned when 50% of subjects were evaluable for the primary end point to determine if the prespecified criteria for bioequivalence were achieved; if demonstrated, the study could be stopped early. The primary end point was area under the concentration–time curve (AUC) of the analyte in plasma from time zero extrapolated to infinity (AUC0–∞ ). Other pharmacokinetic (PK) parameters, safety, and in vitro binding affinity were also evaluated. Results : The interim analysis demonstrated three-way bioequivalence for all comparisons. The confidence intervals around the geometric mean ratios of the primary and secondary PK parameters were within the predefined acceptance ranges. Study drugs were well tolerated with no clinically relevant differences in safety. Conclusion : BI 695502 and US- and EU-approved Avastin showed three-way bioequivalence with similar safety profile. Clinical trial registration : NCT01608087.